Fused roots of maxillary molars: characterization and prevalence in a Latin American sub-population: a cone beam computed tomography study - Maytté Marcano-Caldera; Jose Luis Mejia-Cardona; María del Pilar Blanco-Uribe; Elena Carolina Chaverra-Mesa; Didier Rodríguez-Lezama; Jose Hernán Parra-Sánchez (Restorative Dentistry & Endodontics)
ObjectivesThe upper molars generally have three roots; therefore, different combinations of fusion can occur, increasing the possibility of finding more complex root canal systems. The purpose of this study was to evaluate the prevalence and characterization of fused roots in first and second maxillary molars using cone-beam computed tomography (CBCT) in a Colombian population.Materials and MethodsA total of 1274 teeth were evaluated, of which 534 were maxillary first molars and 740 were maxillary second molars. Axial sections were made at the cervical, middle, and apical levels to determine the prevalence of root fusion and the types of fusion.ResultsOverall, 43% of the molars (n = 551) presented some type of fused root. Root fusion was present in 23.4% of the maxillary first molars. The most frequent type of fused root was type 3 (distobuccal-palatal; DB-P) (58.9%). Root fusion was observed in 57.6% of the maxillary second molars, and the most prevalent type of fused root was type 6 (cone-shaped) (45.2%). Of the maxillary molars, 12.5% were classified as C-shaped.ConclusionWithin the limitations of this study, there was a high prevalence of fused roots in maxillary molars in the Colombian population, mainly in the maxillary second molars. In first molars, the most common type of fused root was type 3 (DB-P) and in second molars, the most common type was type 6 (cone-shaped). Additionally, molars with root fusion presented variation at different levels of the radicular portion, with implications for treatment quality.